Rancang Bangun Sistem Informasi Aplikasi Bank Sampah Menggunakan Framework Laravel Berbasis Website (Studi Kasus : Desa Mekarsari, Jimbaran) - Akasa, Dinda Fatika; Indriyanti, Aries Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
Mekar Sari Jimbaran Village Waste Bank is environmental organizations working in the health sector environment. This activity is carried out by representatives local environmental communities and customers. Garbage bank at Mekar Sari Village is registered in the savings book. Taking citizens' savings cannot be implemented directly, However, it is implemented once and can be withdrawn at any time if necessary. When processing waste bank data, archived documents are still messy, handwritten, and the text is not clear. This often results in errors and loss of data on citizens' savings cycles. This research discusses the development of bank website applications with waste using the Rapid Application Development Method (RAD) as well as deploy system level reception through Technology Acceptance Model (TAM). This website aims to simplify the process of waste management, driving community participation, and increasing transparency finance in the waste bank system. The RAD method is used to speed up the development process with an approach iterative and responsive to user feedback. Results development includes member registration features, transaction management, financial reporting, management systems rewards, and integration with social media.